Optimisme dan Larangan Berputus Asa dalam Tafsir Al-Azhar: Telaah Tematik atas Ajaran Islam dalam Kehidupan Modern - Wais Al Qurni; Arif Firdausi Nur Ramadlon; Indri Astuti (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The Qur'an, as the holy book of Islam, provides comprehensive guidance for life, including teachings that encourage optimism and prohibit despair in the face of life's trials. However, a deep understanding of these messages requires the aid of tafsir (Qur'anic exegesis). This study aims to examine the interpretation of verses related to optimism and the prohibition of despair in Tafsir Al-Azhar by Buya Hamka. The research employs a library method with a thematic approach. The analysis focuses on selected verses such as QS. Ali Imran: 139, QS. Yusuf: 87, QS. Az-Zumar: 53, QS. Al-Anbiya’: 90, and QS. Ash-Shu’ara: 62. The findings indicate that Buya Hamka emphasizes the importance of faith, positive thinking (husnuzhan), and trust in God (tawakkal) as foundations for developing an optimistic attitude. He also asserts that despair reflects a weakness of faith and can negatively affect both individual and social life. This study concludes that Tafsir Al-Azhar not only conveys theological messages but also offers psychological and moral motivation that is relevant to contemporary issues such as depression and suicide caused by life pressures. Therefore, Buya Hamka’s humanistic approach to tafsir is a valuable reference for strengthening the mental resilience of society, fostering patience, and instilling hope in facing life's challenges. Scientifically, this study contributes to the development of thematic Qur'anic exegesis by integrating theological and psychological aspects, as well as humanistic values in a modern context